2013
DOI: 10.1002/ccd.25058
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric patient radiation dosage during endomyocardial biopsies and right heart catheterization using a standard “ALARA” radiation reduction protocol in the modern fluoroscopic Era

Abstract: The use of a novel ALARA protocol for RHC and EMB in pediatric cardiac transplantation patients markedly reduced radiation exposure to levels far below any previously reported values without negatively affecting the safety or efficacy of these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…Cardiologists are discovering that selecting the "low dose" setting does not compromise the ability to carry out certain catheterization procedures. 37 In particular, a combination of very low frame rates (2-3 frames per second), antiscatter grid removal and avoidance of magnification was found to produce an excellent dose reduction for EPS procedures. 38 It should be noted, however, that higher doses can be justified if it can be demonstrated that patient outcome is improved accordingly.…”
Section: 4mentioning
confidence: 98%
“…Cardiologists are discovering that selecting the "low dose" setting does not compromise the ability to carry out certain catheterization procedures. 37 In particular, a combination of very low frame rates (2-3 frames per second), antiscatter grid removal and avoidance of magnification was found to produce an excellent dose reduction for EPS procedures. 38 It should be noted, however, that higher doses can be justified if it can be demonstrated that patient outcome is improved accordingly.…”
Section: 4mentioning
confidence: 98%
“…It remains unknown how low the pulse rates can be to keep acceptable visibility to perform safe and effective catheterization procedures in the PCL. Previous studies have shown the usefulness of very low pulse rate fluoroscopy in certain procedures in the PCL . Sutton et al reported the use of 2‐3 p/s fluoroscopy for right heart catheterization with endomyocardial biopsy .…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the frame/pulse rates of cineangiography and fluoroscopy is one of the approaches for dose optimization in the cardiac catheterization laboratory . Furthermore, lowering the pulse rate of fluoroscopy alone can significantly reduce radiation dosage in the pediatric cardiac catheterization laboratories (PCL) . However, the impact of lowering the frame rate of cineangiography on radiation dosage and procedural safety of catheterization has not been well studied in the PCL.…”
Section: Introductionmentioning
confidence: 99%
“…Small changes in the dose per frame and/or pulse rate can lead to major dose reduction [13, 14], but need to be tested against diagnostic yield and clinical impact.…”
Section: Substantially Reduce or Eliminate Radiation Exposure Of Pmentioning
confidence: 99%